2012
DOI: 10.2135/cropsci2011.05.0279
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Production in the High Winter Stress Climate of the Great Plains of North America—An Experiment in Crop Adaptation

Abstract: The traditional winter wheat {Triticum aestivum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The "niche" available in corn and soybean based rotations to establish legume cover crops after a summer annual is small. In Northern cropping systems, the opportunity to include late-season legume cover crops is greatly enhanced with the inclusion of winter wheat or spring wheat (Triticum aestivum L.) in the rotation and no-till seeding systems [51,52]. Legume cover crop can be grown in a relay cropping system where the legume is frost seeded under winter cereals or grown as a companion crop with spring cereals [35,[53][54][55][56] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The "niche" available in corn and soybean based rotations to establish legume cover crops after a summer annual is small. In Northern cropping systems, the opportunity to include late-season legume cover crops is greatly enhanced with the inclusion of winter wheat or spring wheat (Triticum aestivum L.) in the rotation and no-till seeding systems [51,52]. Legume cover crop can be grown in a relay cropping system where the legume is frost seeded under winter cereals or grown as a companion crop with spring cereals [35,[53][54][55][56] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of these kinds of genes may result in greater intrinsic physical strength of cell walls and membranes in the landraces from higher latitudes, but also may result in differences in the ability to effectively acclimate to cold temperatures. It previously was shown that wheat lines differ in the response to the onset of low temperatures, such that some lines more rapidly and effectively acclimate to the cold than others [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although many genomic regions associated with freezing tolerance have been identified and are being exploited in breeding programs, sufficient winter hardiness of available cultivars continues to be problematic [35]. Greater diversity of sources of cold-tolerant genotypes may contribute to further development of freezing tolerance and winter hardiness; wheat landraces from around the world are potential sources of this diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The species has been identified as a high-priority species in need of urgent collection and characterization as a crop genetic resource in part due to its tolerance for low and erratic temperature fluctuations (Kantar et al, 2015). Local adaptation is critical for the introduction of new crop cultivars into habitats that may differ in abiotic factors such as daylength, elevation, heat unit and moisture availability, frost-free period, soil type, nutrient status, or biotic stresses such as pathogens and other pest populations (Allard and Bradshaw, 1964;Fowler, 2012). The extensive range of Maximilian sunflower suggests the species is capable of adapting itself to a wide range of growing conditions and likely harbors useful traits as a genetic resource.…”
Section: Genetic Characterization Of Maximilian Sunflower For the Devmentioning
confidence: 99%
“…The extensive range of Maximilian sunflower suggests the species is capable of adapting itself to a wide range of growing conditions and likely harbors useful traits as a genetic resource. Local adaptation is critical for the introduction of new crop cultivars into habitats that may differ in abiotic factors such as daylength, elevation, heat unit and moisture availability, frost-free period, soil type, nutrient status, or biotic stresses such as pathogens and other pest populations (Allard and Bradshaw, 1964;Fowler, 2012). The decreasing cost of genotyping has enabled increased evaluation and use of crop wild relatives (Pyhäjärvi et al, 2013;Fang et al, 2014;Anderson et al, 2016), and the development of new crops such as perennial grains (Zhang et al, 2016).…”
mentioning
confidence: 99%